Sustainable Branding - Aleksandar Grubor; Olja Milovanov (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
The relationship between brands and consumers has evolved significantly over time. Companies that own successful brands have the power to modify the existing system of values and behaviors in society and even create a completely new lifestyle. This power is derived from the mass of loyal consumers who permanently follow favorite brands and often strongly identify with them. Given that successful implementation of the concept of sustainability demands changes that trigger mass rather than individuals, such a power of brands is invaluable. However, despite expressing a positive opinion about socially responsible practice, consumers are generally still not ready to change their behavior (attitude-behavior gap). Accordingly, it is necessary to find an interest for consumers in a sustainable lifestyle and to make it available to them in an easy and attractive way. In that sense, sustainable branding and the overall performance of companies are important instruments and generators of change. Thus, the goal of this paper is to highlight the importance of sustainable branding from the standpoint of society, consumers and companies, and to point out strategies for implementation of sustainable values into the brand concept, relying on the results of research and analysis in the given field
Keywords: M310; 330; brand management; green branding; sustainability; sustainable development; sustainable marketing